SINERGITAS KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI BENGKULU DAN BADAN AMIL ZAKAT NASIONAL PROVINSI BENGKULU DALAM PENGELOLAAN ZAKAT - Anggraini, Wiwit (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
The formulation of this research  are: First, how the management of zakat at Badan Amil Zakat Nasional  (BAZNAS) of Bengkulu Province?  Second, what is the role of the Regional Office of the Ministry of Religious Affairs of Bengkulu Province in the management of zakat at the National  Amil Zakat Agency of Bengkulu Province?  Third, how is the synergy between  the Regional Office of the Ministry of Religious Affairs of Bengkulu  Province  and  BAZNAS of Bengkulu  Province  in the manage- ment of zakat? The research  method used is evaluative  method.The study concluded that: first of zakat management at the National Zakat Agency Bengkulu province include charity fund rais- ing, distribution and utilization of zakat. Second, the role of the Regional Office of the Ministry of Religious Bengkulu province in Zakat Management Agency National  Zakat Bengkulu province  is the founder, partner, facilitator, coordinator and motivator  for the management of zakat that is professional  and trustworthy,  strive to increase  the role of zakat to be a professional  institution, transparent trusts and guidance to the empowerment of zakat functionally includes preparation of the materials empowerment of zakat,  preparation of materials  institutional  accreditation zakat,  preparation of materials  certification  institutional  charity, management Unit Gatherer zakat and collect data with regard to the management of zakat on Unit Gatherer zakat in the Office of Religious Affairs Regency  / City. Third,  form synergy  in zakat management is Unit Gatherer Zakat Regional  Office of the Ministry of Religious Bengkulu Province  has been  collecting zakat, infaq and  sadaqah from across the Civil Service through  a system of payroll deductions, held activities in cooperation with the National  Zakat Bengkulu province,  conducting monitoring activities zakat fund management at the national  zakat Agency se City District of Bengkulu province,  Amil zakat Development of technical  guidance and  assistance  Operational national  zakat Agency in accordance with the province  and  the availability of funds each  year